Preparation of Complex Glycans From Natural Sources for Functional Study - Zhang, Qing; Li, Zhonghua; Song, Xuezheng (Frontiers in Chemistry, 2020)
One major barrier in glycoscience is the lack of diverse and biomedically relevant complex glycans in sufficient quantities for functional study. Natural glycans serve as an important source of these glycans and an alternative to challenging chemoenzymatic synthesis. This review discusses preparation of complex glycans from several classes of glycoconjugates using both enzymatic and chemical release approaches. Novel technologies have been developed to advance the large scale preparation of natural glycan. We also highlight recent approaches and methods developed in functional and fluorescent tagging and high performance liquid chromatography (HPLC) isolation of released glycans.